Isolation and Antimicrobial Resistance Profiles of Enterobacteria from Nestling Grey-Breasted Parakeets (Pyrrhura Griseipectus) - Machado,DN (2018)
ABSTRACT The psittacine Pyrrhura griseipectus is a threatened species currently only found in Ceará State, Brazil. A microbiological survey was conducted to determine the composition of the enteric microbiota of this species, as well as the phenotypic profiles of antimicrobial susceptibility presented by the isolates. Cloacal swabs were collected from individual birds and submitted to microbiological processing. Antimicrobial susceptibility profiles were evaluated using the disk diffusion method. Bacteria of the genus Escherichia, Proteus, Citrobacter, Pantoea, Klebsiella, Enterobacter, Morganella, Hafnia, Enterobacter, and Serratia were isolated. The most frequently isolated species were Escherichia coli, Proteus mirabilis and Proteus vulgaris, corresponding to 36.1%, 26.4%, and 8.3%, respectively. Isolates were more frequently resistant to azithromycin and tetracycline, while Escherichia coli was the main species presenting multidrug resistance. In conclusion, free-living grey-breasted parakeets may harbor enterobacteria with high antimicrobial resistance rates.